Predefined-Time Spatial-Temporal Cooperative Guidance Law With Leader-Follower Strategy - Wang, Xu; Cai, Yuanli; Deng, Yifan; Jiang, Haonan (IEEE transactions on aerospace and electronic systems, 2025)
In this article, a 3-D cooperative guidance law using a leader-follower strategy is proposed for a multimissile simultaneous attack on a maneuvering target at an adjustable impact time and desired impact angles. Since the missile terminal guidance phase spans a very short time, predefined-time convergence theory is introduced to design guidance laws. The convergence time of the guidance error is designed as a tunable parameter and can be predefined arbitrarily regardless of the initial conditions or other design parameters. First, an impact-time control guidance law with predefined-time convergence is presented for the leader missile to hit the target at any prespecified impact time. Next, based on the predefined-time adaptive sliding-mode control method, an impact-angle control guidance law is designed to attack the maneuvering target at the desired line-of-sight angles without estimation of the target's acceleration, ensuring that the impact-angle errors converge to a small neighbor of zero at the predefined time. To address the inaccessibility of followers to the leader state under a directed communication topology, a predefined-time cooperative guidance scheme consisting of a distributed state observer and a tracking controller is, subsequently, developed. It utilizes information from neighboring missiles to reach a consensus regarding relative distance and radial relative velocity between the leader and followers, which ensures the simultaneous attack of the missile cluster. A stability analysis of the proposed methods is conducted with Lyapunov theory. The numerical simulation results demonstrate the effectiveness of the proposed cooperative guidance laws.